The Chilean bellflower, Lapageria rosea R. et P. and its Chemistry - Escobar Zapata, Carlos Alfonso (2022)
The Chilean bellflower, or Lapageria rosea, is a climber, endemic to central and southern Chile, whose flowers are mainly red in the wild, but that can appear in different shades when cultivated, they range from white to deep red through pink and light red with white spots. In addition to the historical account of its discovery, and how it came to be considered the national flower of Chile, this review describes the long way to determine the chemical structure of the compounds responsible for the Chilean bellflower’s color, the volatile compounds emitted by the flower and the sugars present in its nectar.